ISOLATION AND ANTIBIOTIC SUSCEPTIBILITY TEST OF PSEUDOMONAS MEMBERS IN THE PUS / WOUNDS INFECTIONS BY UTILIZING VITEK2 SYSTEM IN DUHOK CITY - ABDULLAH, BLAND HUSAMULDEEN (Journal of Duhok University, 2023)
The aim of this study was to determine the rate of Pseudomonas species involved in wound infections. Also, the susceptibility and resistotyping patterns of the isolates to commonly prescribed antibiotics were also studied. During a period of nine months between March and November, 2022, a total of 200 specimens of pus or wound swabs were collected from adults patients that went to the Vin and Emergency Hospital in Duhok City. The samples were plated on Blood agar and MacConkey Agar, and the isolates were identified by the VITEK2 System. Antibiotic susceptibility and resistance profiles for 20 commonly prescribed antibiotics were also performed by the VITEK2 System. Out of the 200 samples collected from wound infections, 43 isolates of Pseudomonas species were identified at a rate of 21.5 % Pseudomonas aeruginosa being more common than the other species, which included 33 isolates (77 %), flowed by 7 P. putida isolates (16 %), and 3 P. fluorescens isolates (7 %). All isolates were obtained from adult patients aged 16–75 years, 29 (77%) of them were isolated from males, while 14 (33%) were isolated from females. The sensitivity patterns showed that Amikacin and Piperacillin-Tazobactam were the most active antibiotics against Pseudomonas aeruginosa, followed by Piperacillin, and then Colistin with Tobramycin. The Meropenem and imipenem show a high level of activity against P. putida and P. fluorescens isolates, while their sensitivity was moderate for Pseudomonas aeruginosa. Also, moderate sensitivity was revealed by Ciprofloxacin, Levofloxacin, and Ceftazidime, while all isolates were resistant to the Cefixime, Ceftriaxone, Cefazolin, Co-Trimethoprim, Amoxiclav, and Amoxiclav, and low sensitivity to Cefepime